SCALAR PERTURBATIONS IN f(R)-COSMOLOGIES - Eingorn, M.; Novak, J. (Одеські астрономічні публікації, 2013)
We take first steps to generalizing the recently developed mechanical (non-hydrodynamical), or discrete (discontinuous), approach to cosmological problems on intermediate, semiastrophysical semicos- mological, scales to the case of nonlinear gravity. In the framework of the f(R) theory we study the scalar perturbations in the flat space and derive the corresponding gravitational potentials.